Avaliação dos fatores que interferem na sedimentabilidade de sistema lodo ativado UNITANK : estudo de caso da estação de tratamento de esgoto sanitário de Mulembá II em Vitória/ES - Uliana, Lorena Fávero (2018)
Activated sludge technology is widely used in the treatment of wastewater around the world. However, its performance is conditioned to an efficient solid-liquid separation. In view of this, this research sought to evaluate the factors that interfere in the sedimentability of sludge from the WWTP Mulembá II, UNITANK activated sludge system, implemented in Vitória-ES. For this, the proposed methodology determined experimentally the sedimentability characteristics of the sludge sampled directly from the WWTP, transcribed in the Vesilind (ke v0) constants and the volumetric sludge index (IVL) and its derivations, besides having verified the correlations that these parameters sedimentability could have with several other operational monitoring parameters of the plant. Finally, the aim was to validate the use of IVL as an indicator of the sedimentation operation of the WWTP Mulembá II. The results of IVL, Diluted IVL (IVLD), k e v0 allowed to characterize the sludge as "good" sedimentability, recording results average of 100 ml/g, 80 mg/l, 0.39 l/g and 13.92 m/h respectively. The most relevant factors that correlated (95% confidence) moderately with the IVLWWTP variable were Nitrogen-NTK, BOD5 in the final effluent and Filamentous Bacteria Count. The variable IVLD obtained a moderate to strong correlation with the factors F/M ratio, dissolved oxygen in the aeration tank and SST in the treated effluent. The variables Relationship IVL30/IVL10 and Relation IVLD30/IVLD10 obtained moderate correlation with Temperature and Filamentous Bacteria Count. At constant k, the factors correlated (95% confidence) moderately with Hydraulic Holding Time in the decanter and Chloride. The constant v0 was only moderately correlated with NitrogenNO3 in the aeration tank. Finally, it can be affirmed that the IVL is a significant parameter to represent the sedimentability characteristics of the WWTP Mulembá II, not dispensing with the need for complementary analyzes to assess the sedimentation process of the WWTP Mulembá II.